Strongly Coupled Cobalt Diselenide Monolayers for Selective Electrocatalytic Oxygen Reduction to H2O2 under Acidic Conditions - Zhang, Xiao‐Long; Su, Xiaozhi; Zheng, Ya‐Rong; Hu, Shao‐Jin; Shi, Lei; Gao, Fei‐Yue; Yang, Peng‐Peng; Niu, Zhuang‐Zhuang; Wu, Zhi‐Zheng; Qin, Shuai; Wu, Rui; Duan, Yu; et al. (Angewandte Chemie International Edition, 2021)
Electrosynthesis of hydrogen peroxide (H2O2) in the acidic environment could largely prevent its decomposition to water, but efficient catalysts that constitute entirely earth‐abundant elements are lacking. Here we report the experimental demonstration of narrowing the interlayer gap of metallic cobalt diselenide (CoSe2), which creates high‐performance catalyst to selectively drive two‐electron oxygen reduction toward H2O2 in an acidic electrolyte. The enhancement of the interlayer coupling between CoSe2 atomic layers offers a favorable surface electronic structure that weakens the critical *OOH adsorption, promoting the energetics for H2O2 production. Consequently, on the strongly coupled CoSe2 catalyst, we achieved Faradaic efficiency of 96.7 %, current density of 50.04 milliamperes per square centimeter, and product rate of 30.60 mg cm−2 h−1. Moreover, this catalyst shows no sign of degradation when operating at −63 milliamperes per square centimeter over 100 hours. A strategy that narrows the interlayer distance of cobalt diselenide (CoSe2) is reported, which enables strong coupling between CoSe2 monolayers. The strongly coupled CoSe2 can catalyze electrosynthesis of H2O2 in acidic media efficiently, which yields Faradaic efficiency of 96.7 %, current density of 50.04 mA cm−2, and product rate of 30.60 mg cm−2 h−1, outperforming all catalysts reported previously in acidic environments.